Analisis Tindakan Sosial Orang Tua dalam Pernikahan Anak Usia Dini di Sulawesi Selatan - M. Ihsan Darwis; Harifuddin Harifuddin (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study aims to (1) explore the social actions undertaken by parents in early childhood marriages and (2) analyze the impacts of early childhood marriages on those involved. The research employs a mixed-methods approach using an exploratory sequential design, integrating qualitative and quantitative methods. The study population includes all early childhood marriages, with a sample size comprising 10%. The informants interviewed were the parents of early-marriage couples. Data collection methods involved in-depth interviews, participant observation, questionnaires, and literature reviews. Qualitative data analysis followed a three-stage technique, while quantitative data analysis employed frequency tabulation. The findings reveal that (1) Social actions in early childhood marriages fall into four categories: instrumental rationality, value rationality, traditional actions, and affective actions. (2) Early childhood marriages result in both positive and negative impacts. Positive outcomes include fostering independence, responsibility, and maturity among the couples, while negative outcomes include family disharmony, emotional instability, and divorce. In conclusion, early childhood marriage couples can be categorized based on four types of social actions, each driven by different motivations for marriage. This study recommends providing guidance and support to all early childhood marriage couples to help them navigate their marital lives successfully.